Covering Canadian crime: what journalists should know and the public should question - Richardson, Chris; Fullerton, Romayne Smith (University of Toronto Press, 2016)
"Crime reporting, in one form or another, is as old as crime itself. Almost all young reporters have spent some time on this beat, and their work affects all of us. Covering Canadian Crime offers a deep and detailed look at perennial issues in crime reporting and how changes in technology, business practices, and professional ethics are affecting today's crime coverage."--